Ethnomedical Study of Plants as a Traditional Medicine on Respiratory System Disease in Cilongok, Banyumas, Indonesia - Retno Wahyuningrum; Dondi Pangestu; Arif Budiman (Faculty of Pharmacy, Universitas Gadjah Mada, 2022)
Indonesia is one of the most geologically complex regions globally and makes it one of the greatest of the world's biodiversity centers. But the primary data on medicinal plants in Indonesia is still lacking. Cilongok is a district in Banyumas located on the slope of Slamet mountain. It is one of the biodiversity areas in Java, Indonesia. Respiratory System Disease has become one of the top ten diseases in Banyumas Indonesia. This study aimed to explore information about the type of medicinal plants used for respiratory system disease and how to process it in Cilongok District, Banyumas Regency, Central Java. This study was descriptive survey research with semi-structured interviews of 68 informants. Data were qualitatively analyzed by interpreting the interview transcript and quantitatively to calculate the Species Use Value of those medicinal plants. The result showed that in Cilongok District, there were 40 medicinal plant species from 25 families used as traditional medicine in respiratory system disease and pounded as the most used method of preparation. Citrus aurantiifolia (Christm.) Swingle is the most used medicinal plant with SUV were 0.235, followed by Amomum compactum Sol. ex Maton (SUV 0.206), Zingiber officinale Roscoe (SUV 0.176), Kaempferia galanga L (SUV 0.176), and Zingiber officinale var Rubrum (SUV 0.147).